Morphologycal and Molecular Partial Histone-H3 Characterization of Bintan Sea Snail Gonggong (Strombus sp.) as a Species Validation - Lily Viruly; Nuri Andarwulan; Maggy T. Suhartono; Mala Nurilmala (Bogor Agricultural University, Indonesia, 2019)
Sea snail gonggong is an icon of Tanjungpinang-Riau Islands Province. It is a favorite seafood item in Riau Islands Province, and is high economic value but not known widely yet. Until now, sea snail gonggong has been highly exploited but the research on this snail is very limited. The aim of this study was to morphology and molecular characterization of Bintan gonggong snail (Strombus sp.) as a species validation. Bintan gonggong snail included thick-shelled gonggong and thin-shelled gonggong. Morphology identifcation of species Bintan gonggong snail was based on morphometric variability. Molecular identifcation used partial Histone-H3, MEGA version 6.06, and bioinformatics analysis. The result showed that the morphological identifcation of thick-shelled and thin-shelled gonggong based on shell width, the lip thickness, and total weight signifcantly diﬀerent, but other variables (i.e shell length, shell depth, aperture length, and gonggong weight) were not signifcantly diﬀerent (p<0.05). Resulted of a molecular identifcation with phylogenetic analysis that the thin-shelled and thick-shelled Bintan gonggong snails were 1 species and a genetic distance of 1%. They were not species Strombus canarium, Strombus vitatus, and Strombus epidromis. Bintan gonggong snails were Strombus turturella (Leavistrombus turturella). DNA sequences of Bintan gonggong have been registered in Gen-Bank with registration numbers MH348131 (thinshelled gonggong) and MH348132 (thick-shelled gonggong).